EMPLOYEE PERFORMANCE IMPROVEMENT STRATEGY AT PT. PERKEBUNAN SUMATERA UTARA - Agung Arinanda; Harmein Nasution; Iskandarini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The purpose of this study was to identify the factors that determine the strengths, weaknesses, opportunities and threats of employee performance at PT. Perekebunan Sumatera Utara. Furthermore, this research aimed to design a strategy to improve the performance of employees of PT Perkebunan Sumatera Utara. The method used in this research was a qualitative method with descriptive techniques, such as data reduction, data presentation and conclusion drawing through SWOT analysis. The results of the study show that the Internal Factors (IFAS) and External Factors (EFAS) Matrix indicates that the performance of employees of PT. Perkebunan Sumatera Utara is still not optimal and requires a strategy to improve. There are several strength factors, namely motivation, relationships between employees, and cooperation & coordination. Meanwhile, the weakness factors of the company are competence, job satisfaction, work experience, and employee loyalty. The opportunity factors of the company are work environment, organizational commitment, and work design. Meanwhile, the threat factors of the company are organizational culture, compensation/honorarium, technology and facilities & infrastructure. While the position of the organization is having strengths but avoiding the threats that exist in the company, PT. Perkebunan Sumatera Utara is required to improve performance in order to achieve the targets of the company's Strenght-Threaths (S-T) strategy by using strengths to face various threats to take advantage of long-term opportunities by means of a diversification strategy (product or market). Improvements can also be made by avoiding micromanagement by building relationships between employees and teamwork and coordination to form an organizational culture that develops behaviors and values for improving employee performance, creating an open door policy in the organization, focusing on diversity and inclusion, increasing employee capabilities by striving to master new technology regarding the products/applications offered to support performance, providing incentives/compensation based on employee work results and improving facilities and infrastructure and providing work support facilities.